Implementation of Project Management Learning Using Trello in an Independent Study Program at VINIX Indonesia - Alyana Isti Hasnani; Dewi, Sinta (Jurnal Serambi Engineering, 2026)
The Independent Study program is designed to enhance students’ practical competencies through project-based learning aligned with industry needs. This study aims to analyze the implementation of Project Management learning in the Independent Study program conducted by VINIX Indonesia. The learning process emphasizes practical project planning, task organization, scheduling, and monitoring using digital project management tools, particularly Trello. This study employed a descriptive qualitative approach by observing learning activities, project documentation, and personal reflections during the program. The results show that the use of Trello supports effective task management, improves project organization, and enhances students’ understanding of project management concepts. The project-based learning approach also strengthens students’ problem-solving skills, teamwork, and readiness for professional work environments. Therefore, the Independent Study program at VINIX Indonesia can be considered an effective learning model for developing project management competencies in higher education.